Mesothelin Expression Is a Predictive Factor for Peritoneal Recurrence in Curatively Resected Stage III Gastric Cancer - Shin, Su‐Jin; Park, Sejung; Kim, Min Hwan; Nam, Chung Mo; Kim, Hyunki; Choi, Yoon Young; Jung, Min Kyu; Choi, Hye Jin; Rha, Sun Young; Chung, Hyun Cheol (The oncologist (Dayton, Ohio), 2019)
Background Mesothelin is overexpressed in many solid tumors, and recent studies have shown that mesothelin expression is associated with poor outcomes in several malignant tumors and may play a role in cancer progression. Clinical trials of mesothelin‐targeted immunotherapies are currently under way, but the correlation between mesothelin expression and gastric cancer prognosis is still unclear. Subjects, Materials, and Methods Mesothelin expression in tumor cells was evaluated immunohistochemically in 958 patients with advanced gastric cancer and interpreted according to the intensity and extent of staining. Samples were scored from 0 to 2, with high expression defined as a score of 2. Clinicopathological factors, overall survival (OS), recurrence‐free survival (RFS), and sites of initial recurrence, including peritoneal recurrence, were evaluated. Staging was performed according to the American Joint Committee on Cancer 7th edition. Results High mesothelin expression was observed in 49.7% of patients and significantly associated with high pathologic T (p = .021) and peritoneal recurrence (p = .018). Multivariate survival analysis showed that high mesothelin expression was independently associated with poor RFS (p = .001), OS (p = .001), and peritoneal recurrence (p = .002) in addition to stage, lymphovascular invasion, and Lauren classification. In a subgroup analysis of peritoneal recurrence, high mesothelin expression was also an independent prognostic factor in stage III (p = .013) and diffuse/mixed type gastric cancer (p = .010). Conclusion High mesothelin expression is correlated with poor outcomes. In addition, mesothelin expression, Lauren classification, and stage are meaningful predictive factors for peritoneal recurrence. Moreover, mesothelin was a significant predictor of a high risk of peritoneal recurrence in patients with stage III gastric cancer. Implications for Practice This study demonstrates that high mesothelin expression correlates with poor outcomes and is a significant predictor of peritoneal recurrence in patients with stage III gastric cancer. This study provides instrumental evidence for designing anti‐mesothelin antibody‐drug conjugate clinical trials in patients with diffuse‐type gastric cancer to reduce their high risk of peritoneal carcinomatosis. 摘要 背景。间皮素在很多实体肿瘤中会过度表达，近期研究表明，间皮素表达与若干恶性肿瘤的预后不良有关，并且可能在癌症进展过程中起到一定的作用。尽管目前正在进行以间皮素为靶标的免疫疗法的临床试验，但是间皮素表达与胃癌预后之间的相关性尚不明确。 对象、材料和方法。我们对 958 例晚期胃癌患者的癌细胞间皮素表达进行了免疫组织化学评估，并根据染色的强度和程度进行了解释。样本得分为 0 到 2 分，而 2 分则定义为高表达。我们还评估了临床病理因素、总生存期 (OS)、无复发生存期 (RFS) 和初次复发部位，包括腹膜复发。根据美国癌症联合委员会第 7 版进行分期。 结果。在 49.7% 的患者中观察到间皮素高表达，且该间皮素高表达与较高的病理性 T (p = 0.021) 以及腹膜复发 (p = 0.018) 显著相关。多因素生存分析表明，除了分期、淋巴血管浸润和 Lauren 分类之外，间皮素高表达还与不良 RFS (p = 0.001)、OS (p = 0.001) 以及腹膜复发 (p = 0.002) 等因素独立相关。腹膜复发的亚组分析表明，间皮素高表达也是 III 期 (p = 0.013) 和弥漫型/混合型胃癌 (p = 0.010) 的独立预后因素。 结论。间皮素高表达与预后不良相关。此外，间皮素表达、Lauren 分类和分期对腹膜复发而言是意义重大的预测因素。而且，间皮素是 III 期胃癌患者腹膜复发高风险的重要预测因素。 实践意义:本研究表明，间皮素高表达与预后不良相关，并且是 III 期胃癌患者腹膜复发的重要预测因素。本研究为设计弥漫型胃癌患者的抗‐间皮素抗体‐药物偶联物临床试验，从而降低腹膜转移的高风险提供了有效证据。 This article examines mesothelin expression with a focus on its potential as a predictive biomarker of peritoneal recurrence after curative surgery and its prognostic significance and association with clinicopathological factors in gastric cancer.